Research on Control Strategy of Electric Mining Dumper Converter - Tao ZHANG; Yaping HE; Xi HE (机车电传动)
Electric mining dumper has been a key research object in mining industry. Owing to its special operating conditions, the control mode of mining dumper needs to be well studied and selected. The control strategy of the dumper was analyzed, and the application scheme of vector control and direct torque control on the converter of the dumper was studied. Finally, the operating conditions of typical mining dumper were selected and the operating performance of the mining dumper under two control strategies was simulated and analyzed. The experimental results showed that the direct torque control for the mining dumper will be more reasonable.